(untitled) (Scientific journal of the Fergana State University, 2024)
The article considers the pandemic as one of the key motifs of post-apocalyptic literature, exploring how it is reflected in works of fiction and what themes and motifs it emphasizes. The approach to the topic of the pandemic in post-apocalyptic literature is considered through the prism of socio-cultural and philosophical contexts, allowing readers to better understand the meaning and role of such works in modern society.